A role of institute of president is in the modern world (Journal of actual problems of jurisprudence, 2018)
The article is devoted a study and analysis of institute of president in the modern world. An attempt to set a role and place of institute of president in the modern systems of rule is undertaken: presidential, parliamentary and mixed. The factors of origin of one or another system of rule are investigational in a concrete country. Considerable attention is spared the American model of presidential rule.Key words: Constitution, state, president, rule, form of the state, system of rule, mixed form of the state, parliamentary rule.